2015
DOI: 10.1007/s10552-015-0650-0
|View full text |Cite
|
Sign up to set email alerts
|

Two-year follow-up of the effectiveness of a multifaceted intervention to improve adherence to annual colorectal cancer screening in community health centers

Abstract: It is possible to achieve high rates of CRC screening over a 2-year period for vulnerable populations using outreach with FIT as a primary strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 9 publications
1
28
0
Order By: Relevance
“…In a small, year 2 follow-up study (N = 124) with EHR-generated reminder letters, mailed FOBT kits, automated phone calls or text, and if needed, a personal phone call, an impressive 89% of participants completed a second FOBT. 32 This study suggests EHR records may facilitate continued screening and that FOBT completion may be aided with automatic calls (and may not require a clinic visit or personal call). However, it is not known if automated calls or texts would be effective in non-urban areas.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In a small, year 2 follow-up study (N = 124) with EHR-generated reminder letters, mailed FOBT kits, automated phone calls or text, and if needed, a personal phone call, an impressive 89% of participants completed a second FOBT. 32 This study suggests EHR records may facilitate continued screening and that FOBT completion may be aided with automatic calls (and may not require a clinic visit or personal call). However, it is not known if automated calls or texts would be effective in non-urban areas.…”
Section: Discussionmentioning
confidence: 93%
“…7,8,2531 Mailed FOBT kits with reminder letters and telephone calls have been effective in promoting initial and repeat screening in predominantly Spanish-speaking patients in an urban FQHC. 32 …”
mentioning
confidence: 99%
“…In community health center settings, Baker et al found that, compared with usual care (computerized reminders, standing orders for home FIT distribution by medical assistants, and clinician feedback on CRC screening rates), patients in an intervention group that also received a mailed reminder letter, a free FIT with low‐literacy instructions, a postage‐paid return envelope, and automated follow‐up telephone and text messages were much more likely than those in usual care to complete screening with a stool test (82.2% vs 37.3%; P < .001) . After 2 years of follow‐up, 71.6% of the intervention group remained fully up to date with CRC screening . Several organizations have compiled valuable resources to facilitate the implementation of multifaceted interventions to increase uptake of and adherence to CRC screening (see Supporting Information).…”
Section: Options For Crc Screeningmentioning
confidence: 99%
“…203 After 2 years of follow-up, 71.6% of the intervention group remained fully up to date with CRC screening. 204 Several organizations have compiled valuable resources to facilitate the implementation of multifaceted interventions to increase uptake of and adherence to CRC screening (see Supporting Information).…”
Section: Interventions To Increase Utilization and Adherencementioning
confidence: 99%
“…Each method has shown some success [1921]; and each has drawbacks, such as privacy limitations [22], cost, logistics or patient perception [2325]. To our knowledge, evaluations of reminder letters have focused on one screening event and one health condition at a time; for example, mammography and breast cancer [26, 27], pap smear and cervical cancer [28, 29], or immunizations and influenza [29, 30].…”
Section: Introductionmentioning
confidence: 99%